(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
Introduction: Cervical cancer is a disease that can disrupt the reproductive organs and is caused by infection with the Human papillomavirus (HPV). Having good knowledge will encourage someone to have a positive attitude towards something, including in this case implementing health messages and taking preventive measures against cervical cancer. The high incidence of cervical cancer is often due to a lack of prevention efforts in women of childbearing age and low interest in early detection. As a result, cervical cancer is often only detected at an advanced stage, so it is known as the silent killer. The aim of this study was to determine cervical cancer prevention behavior in pre menopause women at Community Health Center 1 Depok. Method: The research method uses descriptive. The sample in this study was women aged 40-50 years. The sampling technique used was quota sampling. The sample used was 43 respondents. Data was analyzed using frequency distribution. Result: Most pre-menopausal aged, at first sexual intercourse are not at risk > 20 years old, first marital status, secondary education and not working. Most respondents had positive behavior in preventing cervical cancer. Conclution: Most respondents had positive behavior in preventing cervical